Concomitant Sternal Fractures: Harbinger of Worse Pulmonary Complications and Mortality in Patients With Rib Fractures. Issue 6 (June 2022) - Choi, Jeff; Mulaney, Bianca; Sun, Beatrice; Trimble, Richard; Tennakoon, Lakshika; Spain, David A; Forrester, Joseph D
Background: Sternal and rib fractures are common concomitant injuries. However, the impact of concurrent sternal fractures on clinical outcomes of patients with rib fractures is unclear. We aimed to unveil the pulmonary morbidity and mortality impact of concomitant sternal fractures among patients with rib fractures. Methods: We identified adult patients admitted with traumatic rib fractures with vs. without concomitant sternal fractures using the 2012-2014 National Inpatient Sample (NIS). After 2:1 propensity score matching and adjustment for residual imbalances, we compared risk of pulmonary morbidity and mortality between patients with vs. without concomitant sternal fractures. Subgroup analysis in patients with flail chest assessed whether sternal fractures modify the association between undergoing surgical stabilization of rib fractures (SSRF) and pulmonary morbidity or mortality. Results: Of 475 710 encounters of adults admitted with rib fractures, 24 594 (5%) had concomitant sternal fractures. After 2:1 propensity score matching, patients with concomitant sternal fractures had 70% higher risk (95% CI: 50-90% higher, P < 0.001) of undergoing tracheostomy, 40% higher risk (30-50% higher, P <.001) of undergoing intubation, and 20% higher risk of respiratory failure (10-30% higher, P <.001) and mortality (10-40% higher, P =.007). Subgroup analysis of 8600 patients with flail chest showed concomitant sternal fractures did not impact the association between undergoing SSRF and any pulmonary morbidity or mortality. Conclusion: Concomitant sternal fractures are associated with increased risk for pulmonary morbidity and mortality among patients with rib fractures. However, our findings are limited by a binary definition of sternal fractures, which encompasses heterogeneous injury patterns with likely variable clinical relevance.